ANALISIS KETIMPANGAN PEMBANGUNAN DAERAH SERTA HUBUNGANNYA DENGAN KESEJAHTERAAN MASYARAKAT DI KAWASAN GERBANGKERTOSUSILA PROVINSI JAWA TIMUR - LAILATUL FITRIYAH (Universitas Negeri Surabaya, 2013)
The problem of imbalance income is one of important problem in regioneconomic development at sector GERBANGKERTASUSILA, East Java Province.The purpose of this research was to know the overview of GRDP of regency/city,analyzing imbalance level of income and it correlation with residents prosperityand find where sector giving more contribution for GRDP at year 2007-2011.Data used in this research was secondary data and method of collecting dataused was documentation method. Analysis tool used to know the overview ofGRDP and sector contribution was descriptive analysis. While to know theimbalance level of income used Williamson Index.Result of this research shows that GRDP of regency/city sustainingimprovement annually. The imbalance income at sectorGERBANGKERTASUSILA classified as high (close to 1) and tends to increasedannually. Regency/city which has lower imbalance income with better prosperitylevel was Gresik Regency, Mojokerto Regency, Mojokerto City, and SidoarjoRegency. Whereas regency/city has moderate imbalance income with middle-lowprosperity was Bangkalan Regency. Regency/city sectors contribution dominatedby commerce sector and processing industry sector.Keywords: GRDP, imbalance income, sector contribution